Jogos digitais educacionais nas aulas de Educação Física: Olympia, um videogame sobre os jogos olímpicos - Franco, Laercio Claro Pereira [UNESP] (2014)
The traditional direction of knowledge transmission from older people to younger ones has been changing the paradigms of family education and schools. This is corroborated by several authors, who claim that literacy is no longer exclusive of school, but can also happen outside it with the use of new technologies. Physical Education also feels these symptoms in the process of virtualization of society, however, still slowly and with difficulties in breaking the tradition of exclusive use of the procedural dimension, entering into the attitudinal and conceptual dimensions. This study focuses on the conceptual dimension of school Physical Education, since its objective was the creation of a 3D digital educational game, which deals with the historical and mythological origins of the Olympic and Athletic Games. The construction of this software was based upon the discussions about the presence of new technologies in Education and Physical Education, besides taking into account game theories in general and specifically digital games with educational objectives. Historical aspects of the Olympic Games in Ancient Greece were surveyed for the approach and reproduction in the phases of the proposed game: the Olympia. The production – made by a multi-disciplinary team from Metrocamp/Ibmec Faculties – had financial support from CNPq, thus opening the possibility of hiring modeling and programming companies to complement the game structure. This manufacturing was based on engine Irrlicht, thus opening possibilities of launching the game for Linux and Windows, among others, in low operational capacity computers, which are present in the majority of data processing labs in the Brazilian public schools. A digital pilot game is presented containing one phase: the race, together with questions to be answered by the students on the concepts offered. A second phase, from a total of four, has already begun - the javelin – but has not yet been concluded....